Presença e impacto de Bemisia tabaci (Genn.) (Homoptera: aleyrodidae) em culturas hortícolas em Portugal - Mexia, António (2008)
In Portugal, Bemisia tabaci (Genn.) (Homoptera: Aleyrodidae) was first recorded in 1992, in horticultural crops. Since 1995, it has been an important pest in the Algarve, southern Portugal, where it is present the whole year round, in greenhouse crops, with high infestations during the summer. In 2006, it was installed in Alentejo and in part of Ribatejo e Oeste region. It is a serious problem to several vegetable crops, due to direct damages, but mainly by transmitting plant viruses. The most severely affected crops are greenhouse tomato and cucurbits. IPM is considered the best way to deal with the sustainable management of this problem, but the presence of viruses complicates the implementation of IPM programs. The work presented here gives an overview of the results obtained by the research activities carried out in Portugal concerning B. tabaci: geographical distribution, bioecology, biotypes identification, virus transmission, risk assessment, natural enemies’ survey and control methods. Future research work is suggested.